2021
DOI: 10.22141/1608-1706.2.19.2018.130662
|View full text |Cite
|
Sign up to set email alerts
|

Ювенильный Артрит: Этиология, Патогенез, Современные Аспекты (Обзор Литературы)

Abstract: Þâåíèëüíûé àðòðèò: ýòèîëîãèÿ, ïàòîãåíåç, ñîâðåìåííûå àñïåêòû (îáçîð ëèòåðàòóðû) Резюме. В статье даны современные представления об этиологии, наследственной предрасположенности, иммунопатогенезе ювенильного ревматоидного артрита (ЮРА), одного из наиболее частых и самых инвалидизирующих ревматических заболеваний, встречающихся у детей. Этиология заболевания в настоящее время окончательно не расшифрована, существует лишь ряд более или менее обоснованных гипотез. Среди предрасполагающих факторов важную роль отвод… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been shown that the activity of inflammation correlates with changes in the synthesis of a significant spectrum of immune mediators. At the same time, cytokine proinflammatory cascades in different forms of the disease often differ [40]. The use of MWR in JIA involves the search for a local inflammatory process as a result of biochemical processes of local, complex vascular-mesenchymal tissue reactions in response to injury.…”
Section: Mwrmentioning
confidence: 99%
“…It has been shown that the activity of inflammation correlates with changes in the synthesis of a significant spectrum of immune mediators. At the same time, cytokine proinflammatory cascades in different forms of the disease often differ [40]. The use of MWR in JIA involves the search for a local inflammatory process as a result of biochemical processes of local, complex vascular-mesenchymal tissue reactions in response to injury.…”
Section: Mwrmentioning
confidence: 99%